(untitled) (African Journal of Biomedical Research, 2019)
The market place as an occupational environment can predispose to obesity, mainly due to sedentary nature and enhanced access to food. This study was designed to determine the prevalence and risk factors of overweight and obesity among traders in Abeokuta South Local Government Area, Ogun State, Nigeria. A descriptive cross-sectional research design involving 210 (60.3%) males and 140 (39.7%) females randomly selected from three markets (Panseke, Kuto and Asero markets) was conducted using a systematic random sampling method. A validated semi-structured questionnaire was used to assess their personal and socio-economic characteristics, alcohol consumption, smoking habits and physical activity levels. Nutrient intake was assessed using a validated 24hr Dietary Recall questionnaire. Body Mass Index (BMI) was derived from height and weight measurements; Waist and hip circumference was taken to assess abdominal obesity. The nutrient intake was analyzed using the adapted Total Diet Allowance (TDA) for windows. Data was analyzed using the Statistical Package for Social Sciences (SPSS), version 20. Based on BMI, the prevalence of overweight and obesity was 24% and 3.7% respectively. About 39.4% of the respondents had abdominal obesity. The prevalence of general obesity was significantly higher among females than males (p=0.000). Over one-third (41.4%) of the respondent have low physical activity level. About 14.9% of the respondents smoke cigarrete and more than one-third (35.1%) consume alcohol. More than half (58.6%) of the males and 89.7% of the females had excess calorie intake in the past 24 hours. A significant association was observed between BMI and smoking pattern but there was no significant association between BMI, physical activity and alcohol consumption pattern. Carbohydrate, protein and fat were consumed above the recommended dietary allowance, while respondents had inadequate intake of micro-nutrients, as well as fiber. Obesity is of public health concern, therefore, sensitization focused on lifestyle modification and proper dietary choices should be considered.